The Process of Transferring the Name of a Land Ownership Certificate Based on a Sale and Purchase Agreement in which the Seller Dies and the Heirs Refuse to Sign in Jepara - Alsy, Achmad Irfan Chasani (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The basic concept in buying and selling land is clear and cash. If the concept of light and cash cannot be fulfilled, it does not mean that buying and selling transactions cannot be carried out. The notary will make another instrument, namely by making a sale and purchase agreement (PJB). The deed of sale and purchase agreement (PJB) can be made in 2 (two) forms, namely the sale and purchase agreement (PJB) not yet paid off and the sale and purchase agreement (PJB) in full amount. The binding sale and purchase is considered paid off accompanied by the power of attorney to sell. If the PJB has been paid off but the seller has died then the AJB can still be signed which will be handed down to the seller's heirs. This study uses a sociological juridical approach, with analytical descriptive research specifications. Sociological juridical research is researching and studying law to see the workings of law in an empirical society. The primary data collection technique uses observation and interviews, and secondary data uses document studies and literature studies.